The Dynamics of Sharia Business Law in Responding to Innovations in Digital-Based Islamic Financial Products - Dede Al Mustaqim Mustaqim; Suci Nurlathifah Putri Heryanto (Journal of Islamic Digital Economic and Finance, 2025)
Introduction: Poverty has significant impacts on social, economic, political, and health sectors. To reduce the poverty rate, financial inclusion and ethical financial innovation play a crucial role. In the context of Islamic finance, the emergence of digital-based products such as green sukuk, Islamic fintech, crowdfunding, QRIS, and e-money reflects a rapid integration between Sharia principles and modern technology. However, this evolution also brings new challenges in regulation, supervision, and adherence to the maqashid shariah framework. Objective: This research aims to analyze the dynamics of Sharia business law in responding to the development of innovative Islamic financial products in the digital era. Method: This research uses a qualitative method with a library research approach, examining authoritative sources such as DSN-MUI fatwas, regulations by OJK and Bank Indonesia, and relevant academic journals. Result: The findings show that innovative Islamic financial products significantly contribute to financial inclusion and the transformation of the Islamic economic system. Their development and oversight involve formal mechanisms by Islamic Financial Institutions (LKS), the Sharia Supervisory Board (DPS), DSN-MUI, and financial authorities. DSN-MUI plays a central role in issuing fatwas, while regulatory sandboxes function as testing grounds for new digital products. Implication: This suggests that combining robust planning, Sharia-compliant implementation, and layered evaluation processes can ensure the sustainability of Islamic finance innovation. The integration of ESG (Environmental, Social, and Governance) principles further enhances its contribution to a sustainable economic system. A collaborative approach involving regulators, scholars, industry players, and academics is key to maintaining relevance, integrity, and public benefit in Islamic digital finance.